Technique-aware Digital Embroidery Simulator with Gaze and Voice Interaction - Bozov, Stefan; Zaharieva-Stoyanova, Elena (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This paper deals with problems related to craft software development oriented to handmade embroidery, created as a simulation of the stitching process by following the needle movement path. The paper focuses on human-computer interaction of the application involving gaze- and voice-based interaction to ensure hands-free control of the embroidery process. This approach allows users with physical disabilities to apply the software on the one side; on the other it speeds up the workflow for users without disabilities. Gaze and voice-based interactions are part of whole system architecture. The presented work demonstrates that interaction technologies can be combined with technique-aware embroidery simulation to support inclusive participation in digital craft environments and to facilitate the preservation and sharing of traditional embroidery knowledge.